Study of Diversity of Plants with Respect to Analytical Characters of Tipeshwar Wildlife Sanctuary, Yavatmal District, Maharashtra, India (International Journal of Scientific Research in Science and Technology, 2025)
Tipeshwar Tiger Reserve and Wildlife Sanctuary, situated near Pandarkawada region of Yavatmal, Maharashtra, stands as a hidden ecological treasure, offering a rare opportunity for wildlife enthusiasts to immerse themselves in an undisturbed natural habitat. Present study deals with collection of data using quadrat method and analysis of collected data for analytical characters including frequency of the plant species, density and abundance of plants of Tipeshwar Wildlife sanctuary was done. In this study, 97 different species of 34 angiospermic families including herbs, shrubs and trees from 12 random plots of local forest attached to Tipeshwar Wildlife Sanctuary has been identified and recorded.